2018
DOI: 10.1002/jum.14806
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Early Breast Cancer Response to Neoadjuvant Therapy Using H‐Scan Ultrasound Imaging: Preliminary Preclinical Results

Abstract: Objective— H-scan imaging is a new ultrasound technique used to visualize the relative size of acoustic scatterers. The purpose of this study was to evaluate the use of H-scan ultrasound imaging for monitoring early tumor response to neoadjuvant treatment using a preclinical breast cancer animal model. Methods— Real-time H-scan ultrasound imaging was implemented on a programmable ultrasound scanner (Vantage 256; Verasonics Inc., Kirkland, WA) equipped with an L11–4v transducer. Bioluminescence and H-scan ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…First of all, we considered only women for which both first post-contrast MRI T1 and MRI T2 exams were available ( Figure 1 ). MRI T1 exams allow us to detect tumor characteristics at initial diagnosis regardless of any type of therapy, while MRI T2 exams show tumor properties that are already informative of the therapy efficacy [ 5 , 6 , 7 , 8 , 9 ]. With this kind of analysis, the current work wanted to respond to the request for designing models based on image processing with the aim to predict RFS or BCR “early on” implicitly, including information about the efficacy of the therapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, we considered only women for which both first post-contrast MRI T1 and MRI T2 exams were available ( Figure 1 ). MRI T1 exams allow us to detect tumor characteristics at initial diagnosis regardless of any type of therapy, while MRI T2 exams show tumor properties that are already informative of the therapy efficacy [ 5 , 6 , 7 , 8 , 9 ]. With this kind of analysis, the current work wanted to respond to the request for designing models based on image processing with the aim to predict RFS or BCR “early on” implicitly, including information about the efficacy of the therapy.…”
Section: Methodsmentioning
confidence: 99%
“…One key benefit of NACT consists of the observation of how the tumor changes or evolves during treatment. Some research studies have underlined that the treatment efficacy can already be evaluated through the exams acquired after the early stages of the NACT, or even only after its first cycle [ 5 , 6 , 7 , 8 , 9 ]. In particular, the inclusion of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) in the NACT protocol yields the possibility to identify finer tumor properties that, beyond structural changes in tumor size and shape, could serve as potential earlier indicators of patient Recurrence-Free Survival (RFS) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gary et al [23] used H-scan ultrasound imaging to analyze the nodules in different thyroid glands; the feasibility of H-scan to distinguish different size scatterers in tissues was demonstrated. Khairalseed et al [24] showed that H-scan ultrasound imaging is an effective tissue characterization technique and may have prognostic value in monitoring the response of early cancer to anticancer therapy. Tai et al [25] proposed an adaptive attenuation correction method for H-scan ultrasound imaging using K-means clustering.…”
Section: Introductionmentioning
confidence: 99%
“…The use of noninvasive ultrasound (US) for tissue characterization has been the focus of research efforts for several decades now, where the challenge is to find hidden patterns in the US data to reveal more information about tissue function and pathology that cannot be seen in conventional US images. H-scan US is a new imaging approach that closely links the mathematics of Gaussian-weighted Hermite (GH) functions to the physics of scattering and reflection from different tissue structures [25][26][27][28][29] . Specific integer orders, termed GH n , are related to the nth derivative of a Hermite function.…”
mentioning
confidence: 99%